GERAKAN SOSIAL BARU PADA MUSIK: STUDI ETNOGRAFI PADA BAND NAVICULA - Gunawan Wibisono; Drajat Tri Kartono (Jurnal Analisa Sosiologi, 2016)
Popular music not only being understood as entertainment media. Through audiences, popular music can be used as social movement instrument. This qualitative research using ethnography study as its approach. The subject on this resrach is Navicula band. The result of this stusy show that, the Navicula’s habitus about Tri Hita Karana’s life as a Balinese: the harmony between God, human and nature.Navicula’s cutural capital about knowledge of music as media and strong awareness of environment problems, social capital show their collaboration with several social organization, economic capital comes form album sales, band’s accessories and their concerts. Symbolic capital depicted by the term that Navicula as green grunge gentlemen. Navicula’s New social movement through Navicula’s discography as their messages, Borneo Tour  as new paradigm on collective action, cultural rebellion reflection through Navicula’s merchandise and hearing responses as movement’s impact. The finding on this research is relevant Bourdieu’s theory to depictedabout social praxis systematicly.New media movement theory can be alliance with other theory because its flexible nature to adjust with social dynamic society today.Keywords: New Social Movement, Music, Ethnography. AbstrakMusik popular tidak hanya dipahami sebagai media hiburan semata. Melalui khalayak ramai, music popular bias menjadi alat untuk gerakan sosial. Penelitian ini bersifat kualitatif dengan menggunakan studi etnografi. Subjek penelitian ini adalah band Navicula. Hasil penelitian menunjukkan bahwa habitus Navicula tentang kehidupan Tri Hita Karana sebagai orang Bali; hubungan harmoni antara Tuhan, manusia dan alam semesta. Modal budaya Navicula tentang pengetahuan tentang music sebagai media dan pengetahuan yang kuat tentang masalah lingkungan, modal sosial menunjukkan kerjasama dengan beberapa organisasi sosial, modal ekonomi berasal dari penjualan album, aksesoris band dan konser mereka. Modal simbolik digambarkan dengan istilah Navicula sebagai green grunge gentlemen. Ranah Navicula menjelaskan di ranah jejaring sosial. Gerakan sosial baru Navicula melalui diskografi Navicula sebagai pesan yang disampaikan, Borneo Tour sebagai paradigma baru aksi kolektif, refleksi pemberontakan kultural melalui merchandise Navicula dan responpen dengar sebagai efek gerakan. Temuan penelitian ini menyiratkan teori Bourdieu yang relevan untuk menggambarkan tentang praktik sosial secara sistematis. Teori Gerakan Sosial Baru bisa dielaborasi dengan teori lain karena fleksibel untuk menyesuaikan diri dengan dinamika sosial masyarakat hari ini.Kata Kunci: Gerakan Sosial Baru, Musik, Etnografi.